2019
DOI: 10.1001/jamainternmed.2019.3806
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Diabetes Guideline Frameworks for Individualizing Glycemic Targets

Abstract: IMPORTANCE Diabetes guidelines recommend considering specific factors, such as diabetes duration and life expectancy, to individualize treatment in older adults. These individualized glycemic targets inform decisions on whether to intensify or deintensify medication treatment plans. How older adults with diabetes perceive these factors used to individualize glycemic targets is unknown.OBJECTIVES To examine how older adults perceive factors used in diabetes guidelines for individualizing glycemic targets. DESIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…In our analysis, hypoglycaemia obtained a relative importance with respect to the rest of the attributes, being in line with what has been reported by other studies, in which patients with type 2 diabetes mellitus (T2DM) indicated that the most important factor in both initiating and discontinuing treatment is the risk of suffering adverse effects [40].…”
Section: Discussionsupporting
confidence: 91%
“…In our analysis, hypoglycaemia obtained a relative importance with respect to the rest of the attributes, being in line with what has been reported by other studies, in which patients with type 2 diabetes mellitus (T2DM) indicated that the most important factor in both initiating and discontinuing treatment is the risk of suffering adverse effects [40].…”
Section: Discussionsupporting
confidence: 91%
“…All patients were assigned into the following subgroups according to age and sex: middle-aged (40≤ age <60 years, n = 821) and elderly (age ≥60 years, n = 844) subgroups and male (n = 671) and female (n = 994) subgroups. The inclusion criteria were as follows: age ≥40 years, CAD [ 10 ] (unstable angina; non-ST elevation myocardial infarction; ST-elevation myocardial infarction; and coronary angiography showing the stenosis at least or more than 50% in 1 or more of the left main, left anterior descending, left circumfex, right coronary, or their main branches), and T2DM [ 11 ] (diagnosed according to the American Diabetes Association of diabetes guidelines). The major exclusion criteria included recent acute coronary syndrome, type 1 diabetes or secondary diabetes, connective tissue disease, severe valvular heart disease, constrictive pericarditis, hypertrophic cardiomyopathy, clinical history of malignant cancer, and insufficient medical record for TyG index calculation.…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43] Further, patients with diabetes prioritize addressing symptomatic concerns in complex visits and rate the risk for adverse drug events as the most important factor for choosing a glycemic target. [44][45][46][47][48] The anticipatory guidance for hypoglycemia prevention provided by clinicians in this study was generally consistent with guidelines, although incomplete. Areas that were frequently omitted were treatment of hypoglycemic events and avoidance of driving with hypoglycemia.…”
mentioning
confidence: 73%